The Sangha Education: Phrapariyattidhamma, Dhamma Division - อิทฺธิญาโณ พระครูอุทัยธรรมานุกูล; แสงทองดี ประพันธ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
Dhamma Division in Phrapariyattidhamma education of the Thai Sangha is treated as the heart of the Sangha education system. The education emphasizes the study of Dhamma and Vinaya in order that the monks can practice the Buddhist principles correctly and transfer their knowledge in Buddhism to people accurately. Phrapariyattidhamma education has been treated importantly since the Buddha’s time until now.